(untitled) (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2026)
This study aims to analyse the factors influencing the implementation of Financial Accounting Standards for Micro, Small, and Medium Enterprises (MSMEs) in Semarang City. Specifically, it examines the effects of accounting understanding, information technology utilisation, and MSME owners’ perceptions on SAK EMKM implementation, with SAK EMKM socialisation as a moderating variable. The research employs a quantitative approach using primary data collected through questionnaires distributed to 109 MSME actors selected through purposive sampling. Data were analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM) to evaluate relationships among variables. The results indicate that accounting understanding and MSME owners’ perceptions have a positive and significant effect on the implementation of SAK EMKM. Meanwhile, information technology utilisation shows a significant but suboptimal impact, as technology is still primarily used for operational purposes rather than for financial reporting. In addition, SAK EMKM socialisation does not significantly moderate the relationships between the independent variables and SAK EMKM implementation. The originality of this study lies in the inclusion of SAK EMKM socialisation as a moderating variable and the focus on MSMEs in Semarang City as the research context. This study contributes to the development of accounting practices for MSMEs by emphasising the importance of internal capacity building and more practical-oriented socialisation programs to improve the quality of financial reporting.